Implementasi Kebijakan Pengurusan Surat Keterangan Tidak Mampu Tingkat Rukun Tetangga 007 Jalan Borneo Kecamatan Jekan Raya Kelurahan Palangka Kota Palangka Raya (Studi Komparatif RT 004 Jalan Bukit Raya Kecamatan Jekan Raya Kelurahan Palangka Kota Palangka Raya) - Ego; Saipul (Yayasan Sagita Akademia Maju, 2025)
This study aims to analyze the implementation of the policy for issuing the Surat Keterangan Tidak Mampu (SKTM) at the Rukun Tetangga (RT) level in Palangka Village, Jekan Raya District, Palangka Raya City, with a focus on RT. 007, Borneo Street. The Surat Keterangan Tidak Mampu (SKTM) is an official document issued by the local government (RT, village, or district) that certifies an individual or family as economically disadvantaged. This document is commonly required by the community to access social assistance or public services. The process of obtaining the SKTM, however, often faces challenges, such as a lack of understanding among the community about the procedure, limited resources available to the RT officers, and the potential for misuse of the document if verification is not properly conducted. The research uses a qualitative approach with techniques such as interviews, observation, and document.